VARIABILITY OF THE PRECIPITATIONS REGIME FOR THE FIRST DECADE OF XXIst CENTURY IN SOUTHWESTERN ROMANIA - CRISTINA BURADA; ADRIANA BACESCU; CARMEN MANESCU (Aerul şi Apa: Componente ale Mediului, 2011)
Variability of the precipitation regime for the first decade of XXIst century in southwestern Romania. The first decade of the XXIst century was a period marked by an increase in frequency of extreme weather events. The period analyzed in this paper (2001-2010) was characterized by a high variability in terms of spatial and temporal distribution of precipitation amounts recorded. Some absolute monthly and annual records of rainfall values have been exceeded during this decade in Oltenia (southwestern Romania), standing out the years 2007 and 2008, like dry years, and 2004 and 2005, as excessively rainy years.The aim of this paper is to analyze the spatial and temporal evolution of the annual amounts of rainfall recorded in southwestern Romania between 2001 and 2010. For this paper daily diagnostic data recorded in 14 synoptic weather stations in the Oltenia Regional Meteorological Center were used. The synoptic weather stations with reduced operating hours have been excluded from working in order to limit the errors. We calculated the averages for the past 10 years (2001-2010), for the series of 30 years (1961-1990, 1971-2000 and 1981-2010) and also for the past 50 years (1961-2010) and we compared the obtained values in order to observe the trendline of annual precipitation amounts. We used synthetics graphs and tables for a better overview of the characteristics of the precipitation amounts in the analyzed region.